Penerapan Algoritma Naïve Bayes Dalam Penentuan Kelayakan Penerima Kartu Jakarta Pintar Plus - Endah Widya Ningsih; Hardiyan Hardiyan (Universitas Bina Sarana Informatika, 2020)
The eligibility of Jakarta Smart Card Plus recipients is still not on target due to subjective receipts. Schools has an important role in making decisions about the eligibility of Jakarta Smart Plus Card recipients. Therefore, the authors make this research using data that already exists or is called training data. The author uses the Naïve Bayes method with 7 independent attributes to knowing eligibility. The author also uses the another application Rapidmined 5.3 to test the accuracy of the Naïve Bayes method. The result of this research the accuracy of determining the eligibility of Jakarta Smart Plus Card recipients are good with 98.88% with an error of presentation 2.22%. So it can be concluded that the naive bayes method can help detrermine the eligibility of jakarta smart plus card recipients. Keywords: Jakarta Smart Card, Naïve Bayes, eligibility